Genetic Structure of Lutzomyia longipalpis Populations in Mato Grosso Do Sul, Brazil, Based on Microsatellite Markers - Santos, Mirella F. C.; Ribolla, Paulo E. M. [UNESP]; Alonso, Diego P. [UNESP]; Andrade-Filho, José D.; Casaril, Aline E.; Ferreira, Alda M. T.; Fernandes, Carlos E. S.; Brazil, Reginaldo P.; Oliveira, Alessandra G. (Public Library of Science (PLoS), 2013)
Background:Lutzomyia longipalpis (Diptera: Psychodidae) is the major vector of Leishmania (Leishmania) infantum and thus plays a crucial role in the epidemiology of American visceral leishmaniasis (AVL). This vector is the best studied species of sand fly in the Neotropical region. Many studies claim that this vector is in fact a species complex; however there is still no consensus regarding the number of species that belong into this complex or the geographical distribution of sibling species. The aim of the present study was to analyze the genetic relationships within Lu. longipalpis populations in the state of Mato Grosso do Sul (MS), Brazil.Methodology/Principal Findings:We collected 30 Lu. longipalpis (15 females and 15 males) from five localities (Campo Grande, Três Lagoas, Aquidauana, Miranda and Bonito) and 30 Lu. Cruzi from Corumbá, totaling 180 sandflies from MS, and 30 Lu. longipalpis from Estrela de Alagoas, state of Alagoas (AL), Northeast Brazil. We show that eight previously described microsatellite loci were sufficient in distinguishing Lu. longipalpis from Lu. Cruzi, which is a closely related species, and in differentiating between Lu. longipalpis collected in MS versus Estrela de Alagoas. Analyses of the genotypes revealed introgression between sympatric Lu. longipalpis and Lu. Cruzi.Conclusions/Significance:Our findings support the hypothesis of cryptic species within the Lu. longipalpis complex. Furthermore, our data revealed introgression between Lu. longipalpis and Lu. cruzi. This phenomenon should be further investigated to determine the level and incidence of hybridization between these two species. We also demonstrated that microsatellite markers are a powerful tool for differentiating sand fly populations and species. The present study has elucidated the population structure of Lu. longipalpis in MS and, by extension, the Neotropical Lu. longipalpis complex itself. © 2013 Santos et al.